Aplikasi Pupuk NPK Dan Bokashi Serta Interaksinya Terhadap Pertumbuhan Dan Produksi Tiga Varietas Ubi Kayu (Manihot escculenta. L) Di Kutai Timur - Ratna Shanti; Ratna Nirmala (Universitas Widya Gama Mahakam, 2017)
The purpose of this study to determine the effect of fertilization on the production of three varieties of cassava that is Darul Hidayah, Gajah and Varietas Local. The field experiment was conducted for 9 months starting from April to December 2016. Locations trial in Sangata Selatan, DistrictKutai Timur.The design is split plot design arranged in a factorial treatment was repeated 3 times (R) Treatment Varieties (V) as the main plots and fertilizer treatments (P) as subplot. The results showed that the inorganik fertilizer (NPK), organik (Bokashi) and combinations thereof capable of producing tubers each, 124 tons per hectares, 130.44 tons per hectares, and 134.67 tons per hectares and 99.11 ton per hectares as a kontrol s. Fertilization treatment of three varieties cassava tubers can increase production 20%. 23.8% and 26% respectively as a compared with kontrol s. While the tuber production between varieties Darul Hidayah and Gajah 148.50 tons perhectares and 132, 33 ton per hectares while the local variety 85.33 tons per hectares. The increase in the tubers from 3 varieties namely 42.5% and 35.6% compared to local varieties. Keywords: anorganik and organik fertilizers, varieties of cassava